(untitled) (Bangladesh Journal of Botany, 2025)
For extraction of polysaccharide in staunton vine (PSS), a single factor experiment was carried out to determine the experimental factors and experimental levels. Then in combination with Box-Benhnken central composite design, a response surface analysis was carried out through three factors at three levels in order to evaluate the influence of temperature, ratio of water to material and time on extraction rate of PSS. It is shown by the response surface figure drawn as the extraction rate that the optimal conditions for extraction of PSS include: extraction temperature of 83℃, extraction time of 2.7 hrs and water to material ratio of 30:1 ml/g, and in such case, the extraction rate reached 11.03%. Bangladesh J. Bot. 54(3): 409-417, 2025 (September)